Spiritual values of education on Karate Kid - Yuliana Fatima Dayana; Fachri Helmanto (Mitra Palupi, 2020)
Background: Knowing the movies is most likely a favorite activity, it can take apart in education. Education is one of the important things in our lives. Most adults think